Meningkatkan Hasil Belajar Matematika melalui Model Pembelajaran Realistic Mathematics Education (RME) Berbasis Media Manipulatif - Muhammad Syarwa Sangila; Imaludin Agus; Putri Damayanti (Diniyah: Jurnal Pendidikan Dasar, 2021)
This study aims to improve student learning outcomes in mathematics by applying the Realistic Mathematics Education learning model based on manipulative media in grade IV SD Negeri 04 Wolasi. This type of research is classroom action research. The subjects were 20 students in grade IV SD Negeri 04 Wlasi. The classroom action research design used. The Kemmis and Taggart model which includes planning, action, observation, and reflection. Data collection techniques using observation, interviews, tests, and documentation. The data analysis used descriptive quantitative and qualitative statistics. The results showed that the application of the Realistic Mathematics Education learning model based on manipulative media in Mathematics learning could improve the learning outcomes of fourth-grade students of SD Negeri 04 W0lasi. The improvement of student learning outcomes 35% with an average value of 52.8 in Pre Action Phase, 65% with an average value of 64.75 in cycle I, 90% with an average value of 74.75 in cycle II , and 100% with an average value of 77.4 in cycle III. The increase in student learning outcomes from pre-action to cycle I was 85.71%, cycle I to cycle II was 38.46%, and cycle II to cycle III was 11.11%.Keywords: Mathematics learning outcomes, realistic mathematics education, elementary school